Creating English Textbook to Promote Students' Critical Thinking Skills for 11th Grades Majoring “Marketing” Vocational High School - Sari, Sabrina Mutiara; Muawwanah, Siti; Susanti, Arik (Proceeding of International Joint Conference on UNESA, 2025)
In the demands of 21st-century education, English has a vital role in vocational high schools, preparing for the professional real world. However, vocational high school students focus more on practice than theory, so they do not provide opportunities for them to hone their soft skills optimally. The study aims to create student textbooks that integrate with critical thinking skills, as a companion to student practical activities. This research applies a qualitative descriptive approach according to the ASSURE model, including 1) Analyzing learners' characteristics, 2) Stating objectives, 3) Selecting methods, media, and materials, 4) Utilizing methods, media,and materials, 5) Requiring learner participation, 6) Evaluation and revision. The object is the textbook entitled "Let's Explore Your Social Media Marketing!" which contains 16 pages and 12 activities with some strategies to hone students’ critical thinking skills. The research instrument is secondary data taken from the previous study. Textbook evaluation conducted by feedback from expert validation. The findings indicate a textbook average score of 3.63 which is an excellent category. It isconcluded that the textbook can be a valuable resource for vocational high school students majoring in marketing to develop their critical thinking skills and preparethem for the demands of the 21st-century job market.